Effect of polymer and fiber usage on dewatering and compressibility behavior of fly ash slurries - Cetin, Dogan; Sengul, Tayfun; Bhatia, Shobha K.; Khachan, Mahmoud M. (TAYLOR & FRANCIS INC, 2017)
Coal ash producing is an increasing trend because of its high energy demand worldwide. For transportation, disposal, and reuse of the industrial waste materials, geotextile tube's dewatering technology has been widely used over the last three decades, which helps to decrease the volume of the dewatered slurry. In this study, effect of usage of polymer and fibers on dewatering characteristic of fly ash slurries was investigated. For the experimental investigation, an anionic polymer and short nylon fibers were used. As a new concept, centrifuge test is introduced as an alternative for the widely used pressure filtration test (PFT). Centrifuge test was used to evaluate final solid content of the retained sediments and change in slurry volume of fly ash. Tests were conducted on unconditioned and anionic polyacrylamide and/or fiber conditioned fly ash slurries. Centrifuge test results were compared with PFT results with respect to final solid content. It was found that fiber and/or polymer usage has remarkable effect on the dewatering rate of fly ash slurry. It was also found that final solid content of fly ash slurries was decreased by inclusion of fibers and polymer, which indicates that fiber and/or polymer usage can create more permeable soil body.
Keywords: Centrifuge test; dewatering time; fiber; fly ash; polymer; GEOTEXTILE; FLOCCULATION; TESTS; SAND; Engineering; Oceanography; Mining & Mineral Processing